Stem Cell Therapy for Avascular Necrosis of Femoral Head in Sickle Cell Disease: Report of 11 Cases and Review of Literature - Sadat-Ali, Mir (Int J Stem Cells, 2017)
BACKGROUND AND OBJECTIVE: Sickle cell disease (SCD) is quite common in eastern Saudi Arabia and Avascular necrosis of femoral head (ANFH) occurs in 30% of the young patients leading to early joint arthroplasty. This study was conducted to assess the benefits of injection of osteoblasts in the avascular lesions of the head of femur. PATIENTS AND METHODS: A preset technique was used, 10 CC of bone marrow aspiration was performed under local anesthesia and aseptic technique. Osteoblasts were separated from the bone marrow cells. The avascular area was drilled and 10 million osteoblasts were transplanted at the lesion site. Patients were seen in the out patient clinic after two weeks for removal of the suture and addressed the questionnaire and examined for the range of movement. The follow up MRI was performed at 4 months. RESULTS: The average age was 20.2±3.9 years. The mean hemoglobin S was 81.6±4.8 percent. Quality of Life Score for Chronic Hip Disease was assessed and found at 8.6 (1 being the severe limitation and 10 being normal), whereas Harris hip score improved from 41.7±5.1 to 88.93±3.6 (p<0.001). MRI of pre and post osteoblast implantation showed robust new bone formation and disappearance of the avascular lesions. CONCLUSIONS: The short term results were good and we believe the injection of osteoblast in the avascular lesion of head of femur is a less invasive procedure devoid of any untoward complications and merits such treatment in large patient group with longer follow up.